Objective test findings in patients with chronic eye symptoms seeking care at an outpatient neck center: ligamentous cervical instability etiology? - Hauser, Ross A.; Griffiths, Morgan; Watterson, Ashley; Matias, Danielle; Rawlings, Benjamin (Frontiers in Neurology, 2025)
PurposeTo examine the incidence and potential associations between eye symptoms and objective test findings in patients reporting to an outpatient neck center without known preexisting conditions.MethodsConsecutive patients between January 1 and June 30, 2022, reporting at least 1 of 6 eye symptoms (light sensitivity, blurry vision, eye pain/pressure, vision changes, seeing flashes of light, eye tearing) without known etiology underwent these tests: pupillometry, tonometry, ultrasound of carotid sheath and optic nerve sheath, and digital motion x-ray (videofluoroscopy) and upright cone beam computed tomography scan of cervical spine.ResultsThe analysis included 203/234 consecutive patients. Elevated optic nerve sheath diameter (total >12.2 mm) was documented in 98% (199/203). Supine cervical ultrasound revealed 99.5% (202/203) with internal jugular vein narrowing at C1: total internal jugular vein cross-sectional area <180 mm2. Mean internal jugular vein cross-sectional area at C1 was significantly higher with cervical orthotic Denneroll® (+35.76 mm, p < 0.05). Some 95.6% evidenced vagus nerve degeneration (total cross-sectional area <4.2 mm2) and 86.2% had C1-C2 instability (total >4.0 mm). Pearson correlation coefficient analysis showed a positive relationship between pupil diameter and intraocular pressure (r = 0.29, p < 0.01), while 20.7% had ocular hypertension.DiscussionElevated optic nerve sheath diameter, elevated intraocular pressure, ocular dysautonomia, and succeeding eye symptoms may be pathophysiological effects of internal jugular vein compression and vagus nerve degeneration with underlying ligamentous cervical instability etiology.